Parental exposure to benzo(a)pyrene in the peripubertal period impacts reproductive aspects of the F1 generation in rats - Jorge, Bárbara Campos [UNESP]; Reis, Ana Carolina Casali [UNESP]; Stein, Julia [UNESP]; Balin, Paola da Silva [UNESP]; Sterde, Érika Tissiana [UNESP]; Barbosa, Mariana Gazoli [UNESP]; de Aquino, Ariana Musa [UNESP]; Kassuya, Cândida Aparecida Leite; Arena, Arielle Cristina [UNESP] (Elsevier, 2021)
Benzo(a)pyrene (BaP) is an ubiquitous environmental pollutant which can lead to adverse effects on male reproduction. However, the persistence of these changes on a multigenerational scale has not been sufficiently explored. This study evaluated if peripubertal exposure to BaP in male rats can induce reproductive impairment in offspring. Male rats received BaP at environmentally relevant doses (0, 0.1, 1, or 10 μg/kg/day) orally from post-natal (PND) 23–53. On PND 90, treated males were mated with non-treated females for obtaining the next generation (F1). The paternal exposure to BaP decreased the body weight of offspring on PND 1, 13 and 22, as well as it provoked a reduction in the relative anogenital distance of the males. This exposure also brought forward the onset of puberty, evidenced by an earlier vaginal opening and first estrous in females of the lowest dose group and by a delay in the testicular descent and preputial separation ages in males. The males presented a decrease in the daily sperm production and a disrupted sperm morphology. Furthermore, the testicular histology was altered, evidenced by a reduction in the Leydig cell numbers and in the seminiferous tubules diameter, as well as a disrupted seminiferous tubules staging. The estrous cyclicity and some fertility parameters were changed in the females, as well as alterations in the ovary and uterus histology were observed. BaP compromised several reproductive parameters of the F1 generation, suggesting that peripubertal exposure to this compound provokes permanent modifications in male germ line of F0 generation.
Keywords: Endocrine disruptor; Fertility; Offspring; Paternal programming; Polycyclic aromatic hydrocarbons